Sanitary quality of caprine beef commercialized in fairs of a city in the northeastern hinterland (Research, Society and Development, 2020)
The objective of this study was to evaluate the hygienic-sanitary and microbiological conditions of 08 points of sale in open markets in a city in the northeastern hinterland, located in the São Francisco sub-medium valley, which sell fresh goat meat. The checklist based on RDC No. 216 was applied, and classification according to RDC Nº. 275. Microbiological quality was assessed by counting aerobic mesophilic bacteria, total coliforms, molds and yeasts. The results of the total count of aerobic mesophilic bacteria ranged from 2.5 x 104 to 5 x 105 CFU / g. Total coliform counts were greater than 3 x 104 CFU / g. As for mold, there was no development. For yeasts, the values ​​obtained were 9 x 10² UFC / g. When analyzing the results obtained from the checklist, it was found that all points of sale have irregularities, two classified as Group 2 and six as group 3. From these data, it is concluded that the meat sold in these establishments has a high level of contamination, making them unfit for consumption. Therefore, the present study suggests a set of actions aimed at adapting and training traders in good food handling and conservation practices, and these actions are crucial to prevent food-borne diseases and their aggravation by the pandemic moment.